Qualidade físico-hídrica de um argissolo sob floresta e pastagem no Sul do Brasil - Suzuki, Luis Eduardo Akiyoshi Sanches (2008)
Soil compaction is a problem in different production systems: agriculture, pasture and forest. In the agriculture soil compaction is well documented, while in the pasture and forest its study is scarce. The objective of this study was to evaluate the physical-hydric quality of an Alfisol under forest and pasture in South Brazil, and stabilish parameters and values indicatives of soil quality. The study was carried out in Butiá county, located in the physiographic region of Serra do Sudeste (Escudo Rio- Grandense) in the Rio Grande do Sul state. Four areas were studied: native forest; five-years old pasture, installed under conventional tillage and constituted of Brachiaria brizantha associated with Paspalum lourai and Trifolium sp.; 20-years old Eucalyptus saligna, installed under conventional tillage in 1986; 4.5-years old Eucalyptus saligna in second cycle, where the first cycle was cut 8.5 years after installed. manually and carried out with forwarder. Soil physical properties (bulk density, soil porosity, soil aggregation, air permeability and parameter S), hydrical properties (hydraulic conductivity and soil water retention curve) and mechanical properties (soil penetrations resistance, degree of compactness and compressibility) of soil were evaluated. The depth of soil compaction in the pasture is around 0.10 m, while in the mechanized harvest of eucalyptus may reach 0,40 m, which indicates the need for permanent controlled traffic to minimize soil compaction in forest areas. The critical values of soil physical properties to the growth and yield of annual crops looks effective for perennial and pasture crops. With the increment of soil compaction there is compression of soil aggregates, increase of bulk density and decrease of soil porosity, affecting negatively the fluxes of air and water of soil. Intermediate levels of soil compaction are favorable to the environment, and probably to the plant growth, due to the better soil structure (porosity and bulk density) and greater water availability, along with more efficient to the deformations and susceptibility to compaction. Using bulk density, soil penetration resistance and soil moisture, it is possible to estimate the soil load support ability and its susceptibility to compaction. Biological pores, formed by the action of soil organisms and root decomposition, are effective to increment air flux, fundamental to water infiltration and air flux under conditions of high bulk density. To obtain the reference bulk density to calculate the degree of compactness in forest and pasture, the soil with preserved structure must be sampled in the layer of 0.10 0.125 m, equilibrated under tension of 33 kPa and the reference bulk density must be that obtained from pressure of 1600 kPa.